67.4k views
0 votes
Ab - 3aif a = -4 and b = -2

1 Answer

4 votes

Substitute the given values of a and b into the expression:


ab-3a

If a=-4 and b=-2, then:


ab-3a=(-4)(-2)-3(-4)

Use the order of operations to simplify the arithmetic expression:


\begin{gathered} (-4)(-2)-3(-4)=8-3(-4) \\ =8+12 \\ =20 \end{gathered}

Therefore, the value of ab-3a if a=-4 and b=-2, is:


20

User CharlyDelta
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.